Where Did Spartiates Live? The Lakedaimonian Ōbai and Settlement Patterns in the Spartan Plain from the Archaic to the Roman Period - Christesen, Paul (Classica et Mediaevalia, 2025)
The current scholarly consensus is that, from the Archaic through the Roman periods, all Spartiates belonged to one of five locality-based groupings (ōbai) and that each ōba was linked to a particular settlement nucleus, four of which were located in Sparta and one at Amyklai. All Spartiates thus ostensibly lived in Sparta or Amyklai. Based on a comprehensive review of the textual evidence and an exposition of the relevant archaeological data (which is largely absent from prior treatments of this subject matter), I argue that the city of Sparta was never divided into four ōbai/settlement nuclei and that there was an important element of diachronic change: during the Archaic and Classical periods, Spartiates lived in an unknowable number of ōbai tied to settlements scattered throughout the Eurotas river valley, but, starting sometime in the late fourth or third century BCE most Spartiates found it expedient to live in or near Sparta.